Pre-feasibility study report on a multinational bulk carrier fleet for the Andean Group (Tokyo International Development Center of Japan, 1973)
Informe de proyecto, presenta sumario y conclusiones para el desarrollo de recursos y administracion del transporte de carga en los paises de la Subregion.
Study peformed in accordance with the request of the Junta, Acuerdo de Cartagena and Corporacion Andina de Fomento.
Keywords: CARGA; ESTUDIOS DE VIABILIDAD; PAISES MIEMBROS; PROYECTOS MULTINACIONALES; MARINA MERCANTE